Establishment of stable expression of firefly luciferase and EGFP in a canine inflammatory mammary carcinoma cell line and tumor-bearing model in nude mice - Zhao, Fangying; Li, Xinqiu; Liu, Jiayue; Zhang, Di; Diao, Hongxiu; Lin, Degui (Frontiers in Veterinary Science, 2022)
Canine inflammatory mammary carcinoma (CIMC) is a type of canine malignant mammary tumor with poor prognosis and high mortality. In this study, we transduced firefly luciferase and enhanced green fluorescent protein (EGFP) into CHMp, a CIMC cell line, and established CHMp-Luc-EGFP successfully. In addition, we investigated the characteristics of the cell line in vitro and in vivo. CHMp-Luc-EGFP was cultured in 75 passages, with stable expression of luciferase and EGFP. Compared with the wild type, CHMp-Luc-EGFP had similar proliferation, metastasis, histopathology characteristics, and expression of E-cadherin, N-cadherin, and Ki-67. Tumor-bearing models were established by implantation of CHMp-Luc-EGFP, and the dynamic changes of tumors were visualized and quantified using the IVIS imaging system. In summary, the cell line we established could reflect the biological characteristics of CHMp, visualize the tumor progression in vivo and provide a powerful tool for the study of CIMC.